Numerical Study on Influence of Cross Flow on Rewetting of AHWR Fuel Bundle - Mithilesh Kumar; D. Mukhopadhyay; A. K. Ghosh; Ravi Kumar (The Scientific World Journal)
Numerical study on AHWR fuel bundle has been carried out to assess influence of circumferential and cross flow rewetting on the conduction heat transfer. The AHWR fuel bundle quenching under accident condition is designed primarily with radial jets at several axial locations. A 3D (r, θ, z) transient conduction fuel pin model has been developed to carry out the study with a finite difference method (FDM) technique with alternating direction implicit (ADI) scheme. The single pin has been considered to study effect of circumferential conduction and multipins have been considered to study the influence of cross flow. Both analyses are carried out with the same fluid temperature and heat transfer coefficients as boundary conditions. It has been found from the analyses that, for radial jet, the circumferential conduction is significant and due to influence of overall cross flow the reductions in fuel temperature in the same quench plane in different rings are different with same initial surface temperature. Influence of cross flow on rewetting is found to be very significant. Outer fuel pins rewetting time is higher than inner.